2019
DOI: 10.1093/mnras/stz647
|View full text |Cite
|
Sign up to set email alerts
|

Mode switching and oscillations in PSR B1828–11

Abstract: The young pulsar PSR B1828−11 has long been known to show correlated shape and spin-down changes with timescales of roughly 500 and 250 days, perhaps associated with large-scale magnetospheric switching. Here we present multi-hour observations with the Parkes and Green Bank Telescopes at multiple phases across the ∼500-day cycle and show that the pulsar undergoes mode-changing between two stable, extreme profile states. The fraction of time spent in each profile state naturally accounts for the observed overal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…This can be done either for stars that show some periodic structure in their timing properties (see, e.g., Akgün et al 2006;Ashton et al 2017) or by assuming that some component of pulsar timing noise is due to precession (Cordes 1993). Note, however, that it is by no means clear whether pulsar timing really does provide evidence for free precession (Jones et al 2017;Stairs et al 2019).…”
Section: Signal Strengthmentioning
confidence: 99%
“…This can be done either for stars that show some periodic structure in their timing properties (see, e.g., Akgün et al 2006;Ashton et al 2017) or by assuming that some component of pulsar timing noise is due to precession (Cordes 1993). Note, however, that it is by no means clear whether pulsar timing really does provide evidence for free precession (Jones et al 2017;Stairs et al 2019).…”
Section: Signal Strengthmentioning
confidence: 99%
“…This pulsar is notable for correlated profile and ν changes (Brook et al 2016. Stairs et al (2019) performed an exhaustive analysis on multi-hour long observations of this pulsar and reported that the pulsar undergoes mode-changing between two stable, extreme profile states. They stated that the observed mode transition rate can perhaps be explained by the chaotic behaviour model as previously suggested by Sey-mour & Lorimer (2013).…”
Section: Pulsars With Planetary Companions?mentioning
confidence: 99%
“…They found that the two stable states of this pulsar, namely normal mode and abnormal mode, account for 84.9 percent and 15.1 percent of the total duration, respectively. In the investigation of the young pulsar PSR B1828−11, it was revealed that the pulsar displays two stable modes, the wide mode and the narrow mode, with an estimation of around 500 days for the period of change between the two modes (Stairs et al 2019). Another phenomenon relates to pulse nulling, which could be regarded as an extreme mode changing, and demonstrates as disappearance of pulses for durations ranging from several pulse periods to many years (Wang et al 2007).…”
Section: Introductionmentioning
confidence: 99%